Predictors of thrombotic complications and mass effect exacerbation after pipeline embolization: The significance of adenosine diphosphate inhibition, fluoroscopy time, and aneurysm size. Issue 1 (February 2016) - Raychev, Radoslav; Tateshima, Satoshi; Vinuela, Fernando; Sayre, Jim; Jahan, Reza; Gonzalez, Nestor; Szeder, Viktor; Duckwiler, Gary
Background: The mechanisms leading to delayed rupture, distal emboli and intraparenchymal hemorrhage in relation to pipeline embolization device (PED) placement remain debatable and poorly understood. The aim of this study was to identify clinical and procedural predictors of these perioperative complications. Methods: We conducted a retrospective review of consecutive patients who underwent PED placement. We utilized a non-commercial platelet aggregation method measuring adenosine diphosphate (ADP)% inhibition for evaluation of clopidogrel response. To our knowledge, this is the first study to test ADP in neurovascular procedures. Multivariable regression analysis was used to identify the strongest predictor of three separate outcomes: (1) thrombotic complications, (2) hemorrhagic complications, and (3) aneurysm mass effect exacerbation Results: Permanent complication-related morbidity and mortality at 3 months was 6% (3/48). No specific predictors of hemorrhagic complications were identified. In the univariate analysis, the strongest predictors of thrombotic complications were: ADP % inhibition <49 ( p = 0.01), aneurysm size ( p = 0.04) and fluoroscopy time ( p = 0.002). In the final multivariate analysis, among all baseline variables, fluoroscopy time exceeding 52 min was the only factor associated with thrombotic complications ( p = 0.007). Aneurysm size ≥18 mm was the single predictor of mass effect exacerbation ( p = 0.039). Conclusions: Procedural complexity, reflected by fluoroscopy time, is the strongest predictor of thrombotic complications in this study. ADP% inhibition is a reliable method of testing clopidogrel response in neurovascular procedures and values of <50% may predict thrombotic complications. Interval mass effect exacerbation after PED placement may be anticipated in large aneurysms exceeding 18 mm.